Pollution in Ugandan Cities : Do Managers Avoid It or Adapt in Place? - Bassi, Vittorio; Kahn, Matthew E.; Lozano Gracia, Nancy; Porzio, Tommaso; Sorin, Jeanne (World Bank, Washington, DC, 2021)
Developing countries suffer from rising urban pollution levels, with associated negative effects on health and worker productivity. This paper studies how managers in developing country cities cope with the polluted environment. High-resolution pollution measurements were collected in Ugandan cities and matched with a novel firm survey. The analysis finds that firms locate in close proximity to major polluted roads, which bundle a bad (exposure to pollution) with a good (market demand). Higher ability managers do not avoid polluted areas; instead, they adapt to the pollution by protecting their workers through the provision of equipment and flexibility in work schedule.